Faktor Internal yang Memengaruhi Efektivitas Kinerja Polisi Kehutanan dalam Penanganan Gangguan Kawasan di Taman Nasional Gunung Gede Pangrango - Medi Haerullah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
An effective conservation area is determined by management effectiveness index 70% up (good category). Forest area disruption in the national park is generallycaused by anthropogenic factor. Forest Ranger is one of the significant factors in controlling forest area disruption. Therefore, the purpose of this research is to analyze the performance of forest ranger in handling forest area disruption in Gunung Gede Pangrango National Park (GGPNP). Data were collected by, field observations, and structured interviews using questionnaires. Quantitative data inquiries were done through survey method to all Forest Rangers in GGPNP. The performance of Forest Rangers in GGNP was in medium level with score 21.3. There were 26% of respondents in high level in average (23.1), 68% of respondents in moderate level (20.4), and only 6% of respondents in low level (13.30). The performance of forest ranger in controlling forest area disruption is mainly affected by attitude and motivation.